PENGARUH MEDIA TAMAN HURUF UNTUK MENINGKATKAN KEMAMPUAN PRA MEMBACA ANAK USIA 5-6 TAHUN (Single Subject Research di TK Hidayatul Islamiyah Tahun 2023) - Iis Uswatun Hasanah (Kiddie: Early Childhood Education and Care Journal, 2023)
This study aims to determine the effect of letter garden media to improve pre-reading skills in children aged 5-6 years. This type of research was carried out using the quantitative Single Subject Research (SSR) method, the data obtained through the process of calculating the research results determined by the research instrument. The subjects of this study were 3 children aged 5-6 years in group B Hidayatul Islamiyah Kindergarten, Sumurugul Village. The results of the analysis are in accordance with the data reviewed from the first subject, namely SRP, the length of conditions from Baseline 1, Intervention and Baseline 2 all have 3 sessions. The trend of all graph directions is up. The trend of stability at baseline 1 was 33.3%, at intervention was 66.6% and at baseline 2 was 100%. Data Traces all show results (+). The level of stability at baseline 1 was 33.3% with a range of 10.5% from the lower limit and upper limit data (60.55% -71.05%), at the intervention the level of stability was 66.6% with a range of 11.6% from the lower limit and upper limit data (69.2% -80.8%), then in baseline 2 the stability level is 100% with a range of 13.5% from the lower limit and upper limit data (78.25% -91.75 ). These data indicate an increase in pre-reading skills in SRP by being stimulated using this letter garden media. Based on the results of this study, the teacher implemented fun and innovative pre-reading learning activities with letter gardens. Thus early childhood is easier to recognize letters to improve pre-reading skills.